Stereoselective catalysis of the asymmetric desymmetrization of meso compounds by cinchona alkaloids - Kut, Zeynep Derya. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Asymmetric desymmetrization of meso cyclic anhydrides by selective reaction at one of the enantiotopic carbonyls has attracted considerable attention, because many meso cyclic anhydrides are available through Diels-Alder reactions of maleic anhydride and because the desymmetrized products which contain chemically differentiated carboxy functions can be easily transferred to other versatile chiral building blocks for numerous synthetic applications. In this study, the asymmetric desymmetrization of meso cyclic anhydrides mediated by cinchona alkaloids has been modelled. There are two proposed mechanisms for this reaction; general base catalysis and nucleophilic catalysis. 1. In the nucleophilic catalysis mechanism, the cinchona alkaloid is acting as a nucleophile by making a nucleophilic attack to the meso cyclic anhydride and forming a chiral acyl ammonium salt. This intermediate then reacts with the methanol in the medium yielding the final product. 2. In the general base catalysis mechanism, the cinchona alkaloid acts as a general base rather than a nucleophile.The cinchona alkaloid first reacts with methanol forming a complex. In the second step the methanol of this complex attacks the meso cyclic anhydride causing the ring opening of the anhydride. These two mechanisms have been modelled by using quantum mechanical molecular orbital theory with the aim of explaining the stereoselectivity in the ring opening reactions of meso cyclic anhydrides.
Keywords: Density functionals.